PENGARUH LEVERAGE KEUANGAN, LIKUIDITAS, EARNING PER SHARE DAN RETURN ON ASSET TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR FOOD AND BEVERAGE DI BURSA EFEK INDONESIA - Manik, Denada; Silalahi, Esli; Silalahi, Donalson; Sinaga, Ria Veronica (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
The aim of this research is to determine and explain the influence of financial leverage, liquidity, earnings per share (EPS), and return on assets (ROA) on stock returns in manufacturing companies in the food and beverage sector on the Indonesian Stock Exchange. either simultaneously or partially. The population in this study was 72 companies. The sampling technique used was purposive sampling technique to obtain a sample of 24 companies with a research period of 4 years. The analysis technique used is a multiple linear regression model with descriptive statistical tests, classical assumption tests, and hypothesis testing. The results of the t test research show that the Financial Leverage variable (Debt to Equity Ratio) has a negative and insignificant effect on stock returns, Liquidity (Current Ratio) has a positive and significant effect on stock returns, Earning Per Share (EPS) has a positive and significant effect on stock returns, Return on Assets (ROA) has a positive and significant effect on stock returns in Manufacturing Companies in the Food and Beverage Sector on the Indonesian Stock Exchange. And the results of the F test show that the independent variables, namely Financial Leverage (Debt to Equity Ratio), Liquidity (Current Ratio), Earning Per Share (EPS) and Return On Assets (ROA) have a significant effect on the dependent variable, namely Stock Returns in Food Sector Manufacturing Companies. and Beverage on the Indonesian Stock Exchange. The coefficient of determination is 40.3%, meaning that variations in Financial Leverage (Debt to Equity Ratio), Liquidity (Current Ratio), Earning Per Share (EPS) and Return on Assets (ROA) are able to explain variations in stock returns of 40.3%. Meanwhile, the remaining 59.7% is influenced by other variables.